KOMPOSISI DAN STRUKTUR VEGETASI HUTAN GAMBUT KAWASAN RESTORASI EKOSISTEM RIAU - Fhirgiawan , Sandi Yoga; Satjapradja , Ombo; meiganati, kustin bintani (Universitas Nusa Bangsa, 2022)
Forests have different species and structure compositions depending on local conditions. One of the forests that has a specific character is Peat Forest. The condition of the peat forest footprint explicitly influences the types of flora and fauna that can adapt to the condition of the forest. When there is a disturbance to the peat forest ecosystem, it is necessary to know how the effort is to reverse the condition of the forest ecosystem. Efforts can be made to restore the condition of the ecosystem by restoring the ecosystem. This study aimed to determine the composition, INP, diversity index, and stratification of peat forests in the Riau ecosystem restoration area in Pelalawan District. Data collection methods were carried out with vegetation analysis, field observations, and literature studies. The results of this study indicate that there are 11 species found in the Young Shrub land cover, with the dominant is Ficus carica L, in the Old Shrub land cover found 28 species with the dominating is Shorea sp, while in the Secondary Forest land cover found 55 species, with the type what dominates is the Syzygium sp. The species diversity index in the Young Shrub land cover is of low value, while the Old Shrub and Secondary Forest is of medium value. Based on field observations, canopy closure conditions in the study sites consisted of strata A, B, C, D, and E, which were dominated by Stratum C (4-20 m).